2014
DOI: 10.1099/mic.0.076208-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiological roles of small RNA molecules

Abstract: Unlike proteins, RNA molecules have emerged lately as key players in regulation in bacteria. Most reviews hitherto focused on the experimental and/or in silico methods used to identify genes encoding small RNAs (sRNAs) or on the diverse mechanisms of these RNA regulators to modulate expression of their targets. However, less is known about their biological functions and their implications in various physiological responses. This review aims to compile what is known presently about the diverse roles of sRNA tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
87
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 148 publications
(171 reference statements)
0
87
0
1
Order By: Relevance
“…Among these activities, we identified ethanolamine catabolism, amino acid metabolism, the regulation of carbohydrate metabolism, SRP-dependent cotranslational protein targeting to the membrane, gene silencing, and regulation of plasmid copy number as being represented in both sets (up-and downregulated) of DE sRNAs. A wide variety of studies have revealed that sRNAs are implicated in carbon metabolism, transport, and amino acid metabolism (45), protein transport by SRP-dependent cotranslational protein targeting (57), and control of plasmid copy number (58,59). Some of these processes have been linked to bacterial pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these activities, we identified ethanolamine catabolism, amino acid metabolism, the regulation of carbohydrate metabolism, SRP-dependent cotranslational protein targeting to the membrane, gene silencing, and regulation of plasmid copy number as being represented in both sets (up-and downregulated) of DE sRNAs. A wide variety of studies have revealed that sRNAs are implicated in carbon metabolism, transport, and amino acid metabolism (45), protein transport by SRP-dependent cotranslational protein targeting (57), and control of plasmid copy number (58,59). Some of these processes have been linked to bacterial pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true in the oral cavity, where conditions change daily in short periods of time due to the ingestion of nutrients and to the fact that the oral cavity is an open entrance in contact with the external environment, hence the importance of regulatory elements such as sRNAs, which are rapidly synthesized and capable of modulating the metabolism faster than regulation involving protein synthesis (43,44). It is now well established that sRNAs are capable of performing a wide variety of physiological roles, including adapting to new environmental conditions through quorum-sensing systems or the development of biofilms (45). Recent reports have shown that sRNAs also play important roles in microbial virulence and infection (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Since sRNAs play versatile roles in the bacterial cell, a determined sRNA profile guarantees a quick and precise process of gene regulation and physiological adaptation to an ever-changing environment, which may be necessary for the establishment of a bacterial pathogenic lifestyle (Michaux et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Most sRNAs can be divided into the following four broad categories: (i) cis-acting RNAs; trans-acting RNAs that may either (ii) modulate protein activity or (iii) bind to mRNAs; and (iv) clustered regularly interspaced short palindromic repeats-CRISPRs (Michaux et al 2014b). The most studied bacterial sRNAs are the ones coded in trans, which exert their cellular roles by base pairing with mRNA targets to attenuate, stop, or activate their translation (Man et al 2011;Papenfort and Vanderpool 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These short functional RNAs greatly vary in structure and in mechanism of action. 23,24 To achieve genetic regulation, sRNAs often imperfectly base-pair with a set of given mRNAs, 25 resulting in various outcomes (repression of translation, mRNA degradation or translation enhancement). 23 A single sRNA can even adopt different mechanisms of action depending on the mRNA targeted.…”
mentioning
confidence: 99%